1998
DOI: 10.1111/j.1745-4549.1998.tb00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Oil Content in Fried Processed Sweetpotato Products

Abstract: Ninety‐four different sweetpotato cultivars with various dry matter contents were used to process crisps and the end product was analyzed to determine the oil content. A linear relationship between dry matter content in raw sweetpotato storage roots and the level of oil uptake in crisps was determined. Sweetpotato storage roots with 23–25% (fwb) dry matter content gave crisps containing between 21% and 32% of oil, while the fat contents of crisps from potatoes having a similar dry matter content were 36% and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…This could explain these results. In the case of deepfrying of products, for instance doughnuts and chips, the amount of fat absorption is important due to nutritional concern of high fat intake, as well as the high cost of cooking oil (Hagenimana et al, 1998). In their study a linear relationship was found between dry matter content of the raw sweetpotatoes and the level of oil uptake, therefore, using the right variety will be very important in preparation of these products.…”
Section: Discussionmentioning
confidence: 97%
“…This could explain these results. In the case of deepfrying of products, for instance doughnuts and chips, the amount of fat absorption is important due to nutritional concern of high fat intake, as well as the high cost of cooking oil (Hagenimana et al, 1998). In their study a linear relationship was found between dry matter content of the raw sweetpotatoes and the level of oil uptake, therefore, using the right variety will be very important in preparation of these products.…”
Section: Discussionmentioning
confidence: 97%
“…Sweetpotato as flour or mashed lowered costs and increased the net revenue of snack food sellers and bakers. Mandazi made with mashed sweetpotato absorbs considerably less oil (an expensive ingredient) than those made with wheat flour alone (Hagenimana et al, 1998).…”
Section: I P • S O C I a L S C I E N C E S W O R K I N G P A P E R mentioning
confidence: 99%
“…As such, their consumption is of concern to nutritionists who advocate a decrease or an increase of fat content in the diet depending on the part of the world where they are based. Hagenimana et al [6] found oil to be among the most expensive ingredients in processing home based foods. French fries with lower oil content and equivalent sensory attributes are expected to be accepted by the increasing number of cautious consumers.…”
Section: Introductionmentioning
confidence: 99%